MANFAAT SUPLEMENTASI VITAMIN C PADA KESEHATAN TERNAK RUMINANSIA - Yanuartono Yanuartono; Alfarisa Nururrozi; Indarjulianto Soedarmanto; Dhasia Ramandani (Jurnal Ilmu dan Teknologi Peternakan, 2021)
Vitamin C is an important water-soluble vitamin that is needed by every living thing. Domestic animals, including ruminants, were capable of synthesizing ascorbic acid, primarily in the liver, therefore, vitamin C is not considered to be an essential nutrient for healthy ruminants. Nevertheless, in ruminants, vitamin C is important in biochemical reactions involving collagen cross-linking, hydroxylation of proline and lysine, and steroid and bile acid synthesis. However, in fact, Dietary vitamin C is extensively degraded in the rumen. Although ruminants are able to synthesize vitamin C, when ruminants experience stress and suffer from various diseases, vitamin C supplementation from outside is still needed to restore their health condition. Therefore, vitamin C supplements still have great benefits for optimizing their health conditions. This review discusses the effects of vitamin C and its supplementation on the health of ruminants.